BRG1 interacts with GLI2 and binds Mef2c gene in a hedgehog signalling dependent manner during in vitro cardiomyogenesis. Issue 1 (December 2016) - Fair, Joel; Voronova, Anastassia; Bosiljcic, Neven; Rajgara, Rashida; Blais, Alexandre; Skerjanc, Ilona
Abstract Background The Hedgehog (HH) signalling pathway regulates cardiomyogenesis in vivo and in differentiating P19 embryonal carcinoma (EC) cells, a mouse embryonic stem (mES) cell model. To further assess the transcriptional role of HH signalling during cardiomyogenesis in stem cells, we studied the effects of overexpressing GLI2, a primary transducer of the HH signalling pathway, in mES cells. Results Stable GLI2 overexpression resulted in an enhancement of cardiac progenitor-enriched genes, Mef2c, Nkx2-5, andTbx5 during mES cell differentiation. In contrast, pharmacological blockade of the HH pathway in mES cells resulted in lower expression of these genes. Mass spectrometric analysis identified the chromatin remodelling factor BRG1 as a protein which co-immunoprecipitates with GLI2 in differentiating mES cells. We then determined that BRG1 is recruited to a GLI2-specificMef2c gene element in a HH signalling-dependent manner during cardiomyogenesis in P19 EC cells, a mES cell model. Conclusions Thus, we propose a mechanism where HH/GLI2 regulates the expression ofMef2c by recruiting BRG1 to theMef2c gene, most probably via chromatin remodelling, to ultimately regulate in vitro cardiomyogenesis.